2016
DOI: 10.1016/j.addma.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of physical assets by using ceramic multicomponent extra-terrestrial materials

Abstract: Powder Bed Fusion (PBF) is a range of advanced manufacturing technologies that can fabricate three-dimensional assets directly from CAD data, on a successive layer-by-layer strategy by using thermal energy, typically from a laser source, to irradiate and fuse particles within a powder bed.The aim of this paper was to investigate the application of this advanced manufacturing technique to process ceramic multicomponent materials into 3D layered structures. The materials used matched those found on the Lunar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Objectives of ISRU are, amongst others, the production of propellant, construction materials, life consumables, and metals [6,7,8]. In the literature, many ISRU approaches are discussed, e.g., additive manufacturing [10,11,12], sintering [8,13], or chemical reduction [14] of lunar regolith to name a few. However, to the best of the authors’ knowledge, coating technologies that use regolith as a feedstock have hardly been considered so far.…”
Section: Introductionmentioning
confidence: 99%
“…Objectives of ISRU are, amongst others, the production of propellant, construction materials, life consumables, and metals [6,7,8]. In the literature, many ISRU approaches are discussed, e.g., additive manufacturing [10,11,12], sintering [8,13], or chemical reduction [14] of lunar regolith to name a few. However, to the best of the authors’ knowledge, coating technologies that use regolith as a feedstock have hardly been considered so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has established that PBF can successfully process naturally occurring terrestrial multi-component ceramic materials of igneous origin, which act to simulate a range of key properties such as bulk chemistry, mineralogy and mechanical performance for indigenous materials found on the Moon and Mars. [10][11][12][13] Previous studies related to the concept of 3D printing using extra-terrestrial/astro-materials as feedstock, and their state-of-the art available simulants, [14][15][16] have covered fundamental topics ranging from raw materials' physical properties [17][18][19][20][21][22][23] and their engineering characteristics [24][25][26][27][28] to the development of process parameters 11,13 for the relevant 3D printing technique. Despite all the work that has been done on the research of the materials and manufacturing mechanisms, there is still little information available on the actual mechanical performance of the fabricated components, especially in terms of relating the resulting material microstructure to the processing characteristics and method.…”
Section: Introductionmentioning
confidence: 99%
“…), that would function autonomously and utilise indigenous materials as feedstock [8][9][10][11]. Previous studies have demonstrated that the application of a Powder Bed Fusion 3D printing process can manufacture structures/components from multi component ceramics that closely simulate Lunar and Martian regolith [12,13]. The need to use simulants is due to the scarcity of actual ET materials on Earth; there is a very small, closely guarded quantity of Lunar material and no samples acquired from Mars [14].…”
Section: Introductionmentioning
confidence: 99%